Awareness Regarding Complementary Feeding Among Mothers in a Municipality of Nawalparasi District, Nepal - Bhattarai, Sigma; Bhusal, Chet Kant; Shreesh, Khima (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Complementary feeding is key to promoting healthy growth and development, particularly during the first two years of a child’s life. Lack of awareness and inappropriate feeding practices are a major cause of the onset of malnutrition in young children. The aim of the study was to find out the awareness regarding complementary feeding among mothers in a Municipality of Nawalparasi District, Nepal. MATERIAL AND METHODS Community based descriptive cross-sectional study was conducted to find out the awareness regarding complementary feeding among 67 mothers selected through non-probability convenient sampling technique. Data was collected by using semi-structured interview schedule and was analyzed by using descriptive (frequency, percentage, mean, standard deviation) and inferential statistics (chi square) with Statistical Package for Social Science software (SPSS) version 20.0. The total duration of the study was from September 5, 2018 to September 19, 2018. RESULTS The findings of the study revealed that almost half (47.8%) of the mothers had low level awareness regarding complementary feeding. There was no statistically significant association between respondents’ level of awareness regarding complementary feeding and socio- demographic variables. CONCLUSION Based on the study findings, it is concluded that still half of the respondents had low awareness regarding complementary feeding. If all the mothers were aware regarding complementary feeding. They can prevent the consequences of under-nutrition thereby enabling children to receive appropriate nutrition. Thus it would be recommended to concerned authority to conduct awareness program to mothers regarding complementary feeding.